2018
DOI: 10.3390/genes9090428
|View full text |Cite
|
Sign up to set email alerts
|

Listeria monocytogenes Isolated from Illegally Imported Food Products into the European Union Harbor Different Virulence Factor Variants

Abstract: Unregulated international flow of foods poses a danger to human health, as it may be contaminated with pathogens. Recent studies have investigated neglected routes of pathogen transmission and reported the occurrence of Listeria monocytogenes in food illegally imported into the European Union (EU), either confiscated at four international airports or sold illegally on the Romanian black market. In this study we investigated the genotype diversity and the amino acid sequence variability of three main virulence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 60 publications
3
8
0
Order By: Relevance
“…Our MLST analysis results showed that five CCs were the most prevalent: CC9 ( n = 123 isolates; 26.9%) and CC8 ( n = 82; 17.9%), followed by CC87 ( n = 70; 15.3%), CC155 ( n = 43, 9.4%), and CC121 ( n = 35; 7.6%). These results were consistent with those of previous studies in China (Wang et al, 2012; Li et al, 2018a), France (Felix et al, 2018), the European Union (Rychli et al, 2018), and Spain (Martin et al, 2014). The most prevalent ST was ST9 (26.9%), followed by ST8 (17.9%), ST87 (15.3%), ST155 (9.4%), and ST121 (7.6%) in this study.…”
Section: Discussionsupporting
confidence: 93%
“…Our MLST analysis results showed that five CCs were the most prevalent: CC9 ( n = 123 isolates; 26.9%) and CC8 ( n = 82; 17.9%), followed by CC87 ( n = 70; 15.3%), CC155 ( n = 43, 9.4%), and CC121 ( n = 35; 7.6%). These results were consistent with those of previous studies in China (Wang et al, 2012; Li et al, 2018a), France (Felix et al, 2018), the European Union (Rychli et al, 2018), and Spain (Martin et al, 2014). The most prevalent ST was ST9 (26.9%), followed by ST8 (17.9%), ST87 (15.3%), ST155 (9.4%), and ST121 (7.6%) in this study.…”
Section: Discussionsupporting
confidence: 93%
“…Interestingly, six (100%) ST9/CC9 and one (25%) ST5/CC5 isolates harbored PMSCs in the inlA gene, concurrent with previous studies reported in China (Chen et al, 2018a(Chen et al, , 2019a. Similarly, the PMSCs in the inlA gene were frequent in ST121/CC121 strains, which were predominant in foods and associated environments (Ciolacu et al, 2015;Palma et al, 2017;Rychli et al, 2017Rychli et al, , 2018. These data indicate that the ST9 and ST121 strains predominant in foods may acquire PMSCs in the inlA gene.…”
Section: Discussionsupporting
confidence: 86%
“…Twenty ST155 L. monocytogenes strains, including eleven food isolates and nine human clinical isolates, were used for in vitro virulence assays ( Table 1). The strains from the Unit of Food Microbiology, University of Veterinary Medicine Vienna were isolated in frame of two previous projects [21,47]. Additionally, we screened 477 strains of the internal strain collection by PCR targeting the CC155-specific gene LMLG_RS02400 according to Chenal-Francisque et al [48] and subsequently determined the MLST.…”
Section: Listeria Monocytogenes Strainsmentioning
confidence: 99%